Availability analysis of terrestrial free space optical (FSO) link using visibility data measured in tropical region - Shumani, Mohamed M.; Abdullah, M. F. L.; Basahel, Ahmed (Elsevier, 2018)
Haze and rain are the most impairments factors to free space optical (FSO) links. These weather conditions limit the visibility, and thereby causes high attenuation of the optical signal. This high attenuation reduces the availability performance of the FSO link. This study evaluates the performance of a terrestrial FSO link under tropical climate conditions. The performance analysis is evaluate over 5 km link distance. The cumulative distribution function (CDF) of the received signal to noise ratio (SNR) is used to study the outage performance of the FSO link under haze conditions. The performance analysis is based on three years measured visibility data in Malaysia. Based on the statistical analysis, link availability of 99.99% can be achieved for 37.44 dB SNR over 1 km link distance. Carrier class availability “five nine” can be achieved for 20 dBm transmission power using 1550 nm wavelength.